ANALISIS PRODUK, BRAND IMAGE, DAN PACKAGING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TOKO ROTI WONDER BAKERY DI SURAKARTA - Rangga Indra Fadilla; Ida Aryati; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2019)
This study aims to determine the partial and simultaneous influence of Products, Brand Image and Packaging on Purchasing Decisions of Wonder Bakery Bakery Stores in Surakarta. In this study using quantitative lresearch. Thel populationl inl thisl studyl were consumers of Wonder Bakery in Surakarta. The sample in the study amounted to 100 people. The sampling technique uses accidental sampling, which is sampling taken by giving questionnaires to consumers who make the decision to purchase Roti Wonder Bakery in Surakarta. The F test results show that Products, Brand Image and Packaging Against Purchasing Decisions of Consumers of the Wonder Bakery in Surakarta have a simultaneous effect on the decision to buy wonder bread in Surakarta. Based on the results of testing the partial hypothesis, thel productl hasl al positivel and significant effectl onl thel decisionl tol purchase wonder bakery bread. Brand image has a positive and significant effect on the purchase decision of wonder bakery bread in Jakarta. Packaging hasl al positivel effectl onl thel decisionl to purchase wonder bakery bread. Thel resultsl ofl thel coefficientl ofl determination from the results of analysis calculations can be seen that the number of adjustments R2 obtained is 0.625 or 62.5%. This shows that product quality, brand image, and packaging have an effect on snack purchasing decisions at Wonder Bakery. Keywords: Product, promotion, location, purchasing decision